2020
DOI: 10.1371/journal.pone.0238070
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of SIRPγ on the T-cells of relapsing remitting multiple sclerosis and type 1 diabetes patients could potentiate effector responses from T-cells

Abstract: Factors regulating self-antigen directed immune-responses in autoimmunity are poorly understood. Signal regulatory protein gamma (SIRPγ) is a human T-cell specific protein with genetic variants associated with type 1 diabetes (T1D). SIRPγ's function in the immune system remains unclear. We show that T1D and relapsing remitting multiple sclerosis (RRMS) subjects have significantly greater frequency of rs2281808 T genetic variant, that correlates with reduced SIRPγ-expression in T-cells. Importantly, reduced SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our study highlights SIRPG as a significant marker for DR and its advanced form, PDR, supported by strong evidence. SIRPG, a member of the SIRP protein family, is primarily found on T cells and a subset of B cells ( 23 ). Genomic studies have linked two specific genetic variations of SIRPG, rs2281808 (C > T; intronic) and rs6043409 (G > A; A263 V), to type 1 diabetes ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights SIRPG as a significant marker for DR and its advanced form, PDR, supported by strong evidence. SIRPG, a member of the SIRP protein family, is primarily found on T cells and a subset of B cells ( 23 ). Genomic studies have linked two specific genetic variations of SIRPG, rs2281808 (C > T; intronic) and rs6043409 (G > A; A263 V), to type 1 diabetes ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 79 Accumulating evidence showed that altered expression of genes such as midkine (MDK), 80 CCR2, 81 SAA1, 82 C3, 83 CD19, 84 CCR5, 85 CXCR3, 86 FABP4, 87 GDF15, 88 IGF2, 89 IGFBP1, 90 and IL6 91 is important in the progression of DN. A previous study has shown that UBASH3A, 92 signal regulatory protein gamma (SIRPG), 93 IKZF3, 94 CD1D, 95 CD2, 96 CD48, 97 CD247, 98 and CYP27B1 99 are liable for progression of type 1 diabetes mellitus. The studies have shown that expression of SIT1, 100 junction adhesion molecule like (JAML), 101 TIMP1, 102 protein kinase C beta (PRKCB), 103 MMP7, 104 WNT7B, 105 WNT10A, 106 DUSP1, 107 WT1, 108 APOC3, 109 ERRFI1, 110 HCN2, 111 membrane metalloendopeptidase (MME), 112 STRA6, 113 SLC12A3, 114 and GC vitamin D-binding protein (GC) 115 expedites the epithelial-to-mesenchymal transition and renal fibrosis in DN.…”
Section: Discussionmentioning
confidence: 99%
“…79 Accumulating evidence showed that altered expression of genes such as midkine (MDK), 80 CCR2, 81 SAA1, 82 C3, 83 CD19, 84 CCR5, 85 CXCR3, 86 FABP4, 87 GDF15, 88 IGF2, 89 IGFBP1, 90 and IL6 91 is important in the progression of DN. A previous study has shown that UBASH3A, 92 signal regulatory protein gamma (SIRPG), 93 IKZF3, 94 CD1D, 95 CD2, 96 CD48, 97 CD247, 98 and CYP27B1 99 are liable for progression 128 and UGT2B7 129 to be expressed in obesity. A study has confirmed that altered expression of FCRL3, 130 FCGR2B, 131 cartilage oligomeric matrix protein (COMP), 132 erythroferrone (ERFE), 133 and NPHS1 134 is involved in the progression of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence showed that altered expression of genes such as MDK (midkine) 80 , CCR2 81 , SAA1 82 , C3 83 , CD19 84 , CCR5 85 , CXCR3 86 , FABP4 87 , GDF15 88 , IGF2 89 , IGFBP1 90 and IL6 91 are important in the progression of DN. A previous study has shown that UBASH3A 92 , SIRPG (signal regulatory protein gamma) 93 , IKZF3 94 , CD1D 95 , CD2 96 , CD48 97 , CD247 98 and CYP27B1 99 are liable for progression of type 1 diabetes mellitus. The studies have shown that expression of SIT1 100 , JAML (junction adhesion molecule like) 101 , TIMP1 102 , PRKCB (protein kinase C beta) 103 , MMP7 104 , WNT7B 105 , WNT10A 106 , DUSP1 107 , WT1 108 , APOC3 109 , ERRFI1 110 , HCN2 111 , MME (membrane metalloendopeptidase) 112 , STRA6 113 , SLC12A3 114 and GC (GC vitamin D binding protein) 115 expedites epithelial to mesenchymal transition and renal brosis in DN.…”
Section: Discussionmentioning
confidence: 99%